ANTESEDEN MOTIVASI MINAT MAHASISWA MENJADI ENTREPRENEUR - Nihayatu Aslamatis Solekah; Tri Bagus Doni Andrean (Jurnal Riset Entrepreneurship, 2023)
This study aims to identify the motivation of students' intention to become entrepreneurs in Islamic banking students at UIN Maulana Malik Ibrahim Malang. This research is a quantitative study using an purposive sampling approach with 93 respondents and analyzed using regression analysis. The results show that personal goals, risk tolerance, and readiness for instrumentation affect students' intention to become entrepreneurs. In contrast, work freedom and the need for achievement do not affect student intention. And release in working is due to their ingrained performance as bank employees. The implication of this research is to continue to improve students' soft skills, especially in the spirit of competing or winning competitions, and to change the mindset of students to be free to express their desires in various ways.